Techniczna konstrukcja/odkrywanie prawd (2): martyngał Kartezjusza i miary SI (metr) - Chwałczyk, Franciszek (Humaniora. Czasopismo Internetowe, 2019)
This is the second part of the two-part text based on the works of Martin Hei- degger, Lewis Mumford and Michel Serres. In the first part I analyzed the foundations or the birth itself (the Thales’ discovery – Serres, the ancient myth of the machine – Mumford) of a certain way of producing truths or conditions for recognizing something as true (the Truth). Here, in the second part, I show the discovery of how this Truth works and its development (the Descartes’ discovery, the modern myth of the machine), and thus a significant increase in the ability to produce truths. Continuing recognition made in the first part that – the figure of the essence of technology can be identified with figure of the Truth in this text and that its essence has been a ge-stell – I indicate martingale (Serres) and the myth of balance (Mumford) as ge-stell counterparts. A practical example on which I test the content of both parts of this text are Witold Kula’s research on old measures (part 1) and those from the SI system (in this part).